2011
DOI: 10.5014/ajot.2011.001453
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Occupation and Diabetes Self-Management in Emerging Adulthood

Abstract: I present the findings of a study aimed at developing an in-depth understanding of how engagement in occupation influences young adults' ability to effectively manage diabetes and, conversely, how their diabetes self-management strategies shape their occupational participation. The qualitative interview-based study of 8 people ages 19-25 with Type 1 diabetes revealed that study participants often experienced tension between diabetes self-management and participation in valued occupations, which required them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(110 citation statements)
references
References 17 publications
6
101
0
3
Order By: Relevance
“…Firstly, they draw attention to the fact that young adults in their mid to late twenties can struggle with diabetes management routines and timetables just as much as their younger counterparts. The difference is that younger adults, in their late teens, are often obviously 'out of control' and/or are managing their diabetes in environments that are almost natively inimical to diabetes management (such as the first year of university) (Pyatak, 2011). Young adults in the second phase of young adulthood experience many of the same difficulties, but do so in environments that seem on the face of it to be quite positive for diabetes control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, they draw attention to the fact that young adults in their mid to late twenties can struggle with diabetes management routines and timetables just as much as their younger counterparts. The difference is that younger adults, in their late teens, are often obviously 'out of control' and/or are managing their diabetes in environments that are almost natively inimical to diabetes management (such as the first year of university) (Pyatak, 2011). Young adults in the second phase of young adulthood experience many of the same difficulties, but do so in environments that seem on the face of it to be quite positive for diabetes control.…”
Section: Discussionmentioning
confidence: 99%
“…It would be helpful if diabetes clinics drew up country specific advice for young adults who are considering travelling for workrelated reasons, given the impacts that changes in environments can have on diabetes management (Pyatak, 2011). It would be useful if clinics provided these young adults with telesupport and advice while they were abroad.…”
Section: Discussionmentioning
confidence: 99%
“…Brown and Hanis (2014) also observed that group members from their numerous studies initiated and maintained relationships outside of their research groups. Pyatak (2011b) found that new occupational demands required decision-making and problem-solving that competed with preferred occupations of non-Hispanic white emerging-adults with T1DM. Subsequently, the occupations of diabetes were ignored.…”
Section: Importance Of Traditional Food and Socializationmentioning
confidence: 98%
“…Pilot intervention studies were: Piven & Duran, 2014;Haltiwanger & Galindo, 2013;Haltiwanger, 2012a;Haltiwanger, 2012b;Haltiwanger & Brutus, 2012). Exploratory studies were also published (Thompson, 2014;Fritz, 2013;Pyatak et al, 2013a;Pyatak et al, 2013b;Piven & Nazeran, 2013;Pyatak, 2011a;Pyatak, 2011b;Hwang et al, 2009), suggesting the need for intervention.…”
Section: Implications For Practicementioning
confidence: 98%
“…Recently, some occupational therapists have initiated research in secondary prevention with Mexican-Americans using a group or population-based intervention, in order to prevent the tertiary complications of uncontrolled diabetes before they occur [3,4]. Other occupational therapists have provided a more individual approach to secondary prevention for people with diabetes [5,6]. This is a well-executed small pilot study of 43 temporarily unemployed Hispanic-American males.…”
mentioning
confidence: 99%